Time between symptom and testing in relation to familial transmission of severe acute respiratory syndrome coronavirus 2 - Menezes, Daiane Cabrera [UNESP]; Perico, Jonatas [UNESP]; Martins, Bruna Letícia [UNESP]; Belone, Andrea de Faria Fernandes; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Santana, Fabiana Covolo de Souza; Latini, Ana Carla Pereira [UNESP]; de Souza, Vania Nieto Brito [UNESP] (FapUNIFESP (SciELO), 2023)
Brazil has a huge number of cases and deaths due to coronavirus disease 2019 (COVID-19); however, few studies have dealt with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among familial contacts in Brazil. Here, we report our findings on transmission in a family-based study in Bauru, São Paulo, Brazil. The study, conducted from July to November 2020, comprised 974 individuals with 233 index patients and 741 familial contacts. Familial contacts were evaluated using the rapid COVID-19 Ag ECO and reverse transcription-polymerase chain reaction (RT-PCR) tests immediately after the index patient diagnosis. The antigen-based rapid test was validated in 121 individuals using RT-PCR as the gold standard. Additionally, 30 days later, familial contacts were evaluated for IgM and IgG antibodies against SARS-CoV-2. We found 333 cases of COVID-19 among familial contacts (44.9%). A positive correlation was observed between the time elapsed from the onset of symptoms until the index patient’s COVID-19 testing and the number of family contacts infected by SARS-CoV-2. Early SARSCoV-2 testing and familial contact evaluation are relevant strategies to contain transmission.
Tempo entre o início dos sintomas e a testagem está relacionado à maior transmissão de SARS-CoV-2 entre contatos familiares
Keywords: COVID-19; Pandemic; SARS-CoV-2